AL-CHÄL (ADVERBIA CIRCUMSTANSIAL) DALAM BAHASA ARAB Tinjauan Sintaksis - , Alif Cahya Setiadi, Prof. DR. Syamsul Hadi, SU., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis is a research concerns the system of circumstantial adverbs in Arabic as an inflective language. A research which has accentuated the concepts of adverbs in Arabic, circumstantial adverbs, and the aspect of syntax of circumstantial adverbs in this language. In this case, syntax approach has been used to analyze the structure of Arabic circumstantial adverbs, neither in structure, unit, or the matters which show the connection between words in a sentence. Finally, the concept of Arabic adverbs will be outlined in general linguistic classification. In the step of analyzing, this research used distributional method to analyze the structure and unit of syntax according to itâs unit and influence. Generally, this method has three steps of analyzing in this research, first: finding and explaining the base of adverbs in Arabic. Second: analyzing a category, function, and character of circumstantial adverb, and third: classification and mapping the syntaxâs construction process of circumstantial adverb in Arabic. In order to analyze this circumstantial adverb according to general linguistic view, this thesis used identity method such as referential method and translational method. This research concludes several main point, first: the concept of Arabic adverbs outlined in al-mukammilÄt or al-fudhlah or complement. Substantially, this is a part of speech although categorically itâs unclassified yet as in general linguistic. Second: circumstantial adverbs or al-chÄl is part of Arabic adverbs which describes circumstances of the companion of al-chÄl and itâs regent. Alch Äl or circumstantial adverbs just not only describes circumstance, but also shows an adverb of manner and quality both of companion of al-chÄl and itâs regent. Third: in the syntax consideration, circumstantial adverbs (al-chÄl) stand on every units of syntax such as word, phrase, clause, and sentences. Every units of circumstantial adverb has some role according to the base construction. This circumstantial adverb and both of companion and regent have a changes of position (aâr-ratbah), multi forms (taâaddud), and ellipsis (al-chadzfu).